Identification of the bHLH Transcription Factor Family in Orah Mandarin and the Response of CrbHLH46 to Low-Temperature Stress - Chaoying Chen; Xulin Li; Ke Wen; Tuo Yin; Ping Tian; Ke Zhao; Li Zhang; Xianyan Zhou; Xiaozhen Liu; Hanyao Zhang (Plants)
As the second largest family of transcription factors (TFs) in plants, basic helix–loop–helices (bHLHs) play key roles in regulating plant growth and development and responding to environmental stress. As the fastest growing Citrus variety in China in recent years, Orah mandarin has vital economic and nutritional value. Although a comprehensive genome-wide analysis of the bHLH TF family has been performed in many plants, a systematic study of the genes of this family has not been carried out in Orah mandarin. In this study, 114 bHLH TFs were identified in Orah mandarin via genome-wide analysis and were classified into 27 subfamilies according to the evolutionary tree. The gene expression profile revealed that five genes were significantly upregulated at 12 h and 24 h after low-temperature stress treatment. In addition, soluble sugars, soluble proteins, and proline contents increased with increasing low-temperature stress, which promoted the expression of the CrbHLH46 gene, thus mediating the interconversion pathway of pentose and glucose to improve the cold tolerance of Orah mandarin. The results help explore the characteristics and functions of CrbHLH genes and provide a basis for further research on the Orah mandarin resistance to low-temperature stress.